2015
DOI: 10.5588/ijtld.14.0651
|View full text |Cite
|
Sign up to set email alerts
|

Disputed <I>rpo</I>B mutations can frequently cause important rifampicin resistance among new tuberculosis patients

Abstract: Disputed rpoB mutations may be responsible for the majority of rifampicin (RMP) resistance among new cases, and lead to adverse outcomes of first-line treatment. Silent mutations do not necessarily cause Xpert or line-probe assay false RMP-resistant results. Molecular RMP DST could greatly simplify resistance surveillance, in addition to offering the best prospects for early and accurate individual diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
67
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(73 citation statements)
references
References 0 publications
3
67
2
Order By: Relevance
“…In contrast, a portion of the isolates with intermediate resistance and substitutions in codons 516 and 526 were identified as susceptible by Bactec MGIT 960, which was in line with previous reports [12]. Previous reports noted the clinical importance of “disputed” mutations in the rpoB gene [34, 35, 36]. Because the standard treatment of these patients might result in a poor clinical outcome [37, 38], the use of higher doses of RMP [25] or substitution with RFB [39] is proposed.…”
Section: Discussionsupporting
confidence: 87%
“…In contrast, a portion of the isolates with intermediate resistance and substitutions in codons 516 and 526 were identified as susceptible by Bactec MGIT 960, which was in line with previous reports [12]. Previous reports noted the clinical importance of “disputed” mutations in the rpoB gene [34, 35, 36]. Because the standard treatment of these patients might result in a poor clinical outcome [37, 38], the use of higher doses of RMP [25] or substitution with RFB [39] is proposed.…”
Section: Discussionsupporting
confidence: 87%
“…In addition, molecular studies indicate that it is also important to take into consideration the geographic distribution of different mutation types. It has been shown that in several regions, less common mutations can be significantly more common, and commercial molecular tests may not always detect these mutations (12,13). If the type of mutation is not known to the laboratory scientist or the clinician, it is not possible to draw meaningful conclusions for designing an appropriate drug regimen.…”
Section: (Ii) Is It Important To Have Information On the Type Mutatiomentioning
confidence: 99%
“…In addition, it is clear that some of these less common mutations, which may reach 22% of all RIF-resistant cases in certain areas (14,15), are associated with a phenotypic RIF resistance of Ͻ1.0 g/ml, which is also the definition criteria for MDR-TB. Preliminary results indicate that patients with such mutant strains may fail more often under firstline therapy with standard RIF doses (13). Therefore, future molecular tests must be able to adequately identify these mutations as well.…”
Section: (Ii) Is It Important To Have Information On the Type Mutatiomentioning
confidence: 99%
“…[72] However, the general problem faced at the moment is that the predictive value of resistance mutations is not always clear, especially when they are rarely encountered. [73] For the frequently observed mutations tested in reverse line blot assays, such as the ones associated with rifampicin and isoniazid, the positive-and negative-predictive value is high and this merits direct clinical use of these test results to steer the treatment. [74] For other drugs, especially of the second-line category (Table 2), the predictive value is sometimes somewhat lower and this confuses the utility of this information.…”
Section: Molecular Testingmentioning
confidence: 99%